Does des-acyl ghrelin improve glycemic control in obese diabetic subjects by decreasing acylated ghrelin levels? - Özcan, Behiye; Neggers, Sebastian J C M M; Miller, Anne Reifel; Yang, Hsiu-Chiung; Lucaites, Virginia; Abribat, Thierry; Allas, Soraya; Huisman, Martin; Visser, Jenny A; Themmen, Axel P N; Sijbrands, Eric J G; Delhanty, Patric J D; et al. (European journal of endocrinology, 2014)
ObjectiveThe objective of this study was to assess the effects of a continuous overnight infusion of des-acyl ghrelin (DAG) on acylated ghrelin (AG) levels and glucose and insulin responses to a standard breakfast meal (SBM) in eight overweight patients with type 2 diabetes. Furthermore, in the same patients and two additional subjects, the effects of DAG infusion on AG concentrations and insulin sensitivity during a hyperinsulinemic–euglycemic clamp (HEC) were assessed.Research design and methodsA double-blind, placebo-controlled cross-over study design was implemented, using overnight continuous infusions of 3 and 10 μg DAG/kg per h and placebo to study the effects on a SBM. During a HEC, we studied the insulin sensitivity.ResultsWe observed that, compared with placebo, overnight DAG administration significantly decreased postprandial glucose levels, both during continuous glucose monitoring and at peak serum glucose levels. The degree of improvement in glycemia was correlated with baseline plasma AG concentrations. Concurrently, DAG infusion significantly decreased fasting and postprandial AG levels. During the HEC, 2.5 h of DAG infusion markedly decreased AG levels, and the M-index, a measure of insulin sensitivity, was significantly improved in the six subjects in whom we were able to attain steady-state euglycemia. DAG administration was not accompanied by many side effects when compared with placebo.ConclusionsDAG administration improves glycemic control in obese subjects with type 2 diabetes through the suppression of AG levels. DAG is a good candidate for the development of compounds in the treatment of metabolic disorders or other conditions with a disturbed AG:DAG ratio, such as type 2 diabetes mellitus or Prader–Willi syndrome.